Pure ovarian choriocarcinoma - an aggressive and rare entity - Priyanka Narang; Shivani; Parveen Rana; Pinkey Lakra; Vijayata Sangwan; Kulvinder Singh (Barpeta Obstetrics and Gynaecological Society, 2023)
Pure ovarian choriocarcinomas are exceedingly rare cancers that develop from either the ovary's gestational tissue (ovarian ectopic pregnancy) or the ovary's pure germ cells. They are divided into two types: gestational ovarian choriocarcinoma (GCO) and non-gestational choriocarcinoma (NGC) based on their origin (NGCO). The presence of GCO is indicated by a history of amenorrhoea with sexual intercourse, very high serum beta hCG levels, and the appearance of choriocarcinoma with a corpus luteal cyst in histology, but the DNA polymorphism and presence of paternal DNA in the tumour clinches the diagnosis. Cytoreductive surgery and adjuvant chemotherapy are the mainstays of treatment for pure ovarian choriocarcinomas. Here we present a case of pure ovarian choriocarcinoma, likely of gestational origin.